Jilbab, Hijab Dan Telaah Batasan Aurat Wanita - Roziqin, Ahmad Khoirur (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2018)
Hijab or headscarves in Indonesian terms are clothes that cover a woman’s body, which is also God’s command in the Koran. Although there are small number of Ulama who argue that it is not an obligation because they do not us command verb (fi’il amr). The different is even more striking not obligatory or not because the majority of Ulama sya that hijab or headscarves is obligatory ot in ither terms the obligation to wear hijab for women. But the main point in this paper is which part of the woman’s body that must be closed. Whether all body or any party of the body that may be opened. It is important ti discuss woman’s genitals because in some areas of Islam, there are those cover all the bodies and some other areas that show face and two palms. Therefore, more extensive research is needed in discussing this matter. Plus it is strengthened by opinions of Ulama, in order too enlighten the views of Islamic people in the issue of hijab or headscarves.